Frequency and Outcome of Mitral Regurgitation in Acute ST-Elevation after Myocardial Infarction (Medical Forum Monthly, 2024)
Objective: Determine the frequency and Outcome of Mitral Regurgitation in Acute ST-Elevation after Myocardial Infarction.Study Design: Experimental / Observational studyPlace and Duration of Study: This study was conducted at Cardiology Department, Idris Teaching Hospital Sialkot Medical College Sialkot from Jan 2018 to May 2019.Materials and Methods: 350 Patients from Cardiology department of Idris teaching Hospital Silakot Medical College Sialkot were enrolled in study after fulfilling the inclusion criteria. Procedure of research was explained to the patient and informed consent was taken. Demographic data, name, age, gender, and address was recorded on the attached proforma. Patients were assessed on transthoracic echocardiography by the consultant for presence or absence of mitral regurgitation. Severity of MR will act as effect modifier and was addressed through stratification. Patients were kept in the ward for at least three days. They were examined by the ward consultant for pulmonary edema (fine inspiratory basal crepitation on chest auscultation) or Death (No electrical activity on ECG) immediately after diagnosis of mitral regurgitation and then every eight hours for the following three daysResults: Out of 350 patients (54.3% females). 38.6% patients suffered from MR as the complication of MI. of all the patients who suffered from MR, 68.1% suffered from mild, 21.5 % from moderate and 10.4% suffered from severe grade of MR. 12 % of the patients died and 46.7 % developed acute pulmonary edema after development of MR as a complications of MI. The study also shows that mostly patients suffering from MR after AMI were elderly and female, 52.5 % and 62.2 % respectively.Conclusion: This study demonstrates that there is high frequency of Ischemic Mitral Regurgitation (IMR) after MI in our population and mostly sufferers of this complication are female and elderly population. IMR if present after MI is associated with poor outcome in terms of death and acute heart failure.